Measuring rural women’s time: A theoretical and methodological reflection in agricultural contexts in Argentina - Pessolano, Daniela (2025)
Time-use surveys are a strategic tool to measure the consequences of the sexual division of labor. Their application in Latin America and the Caribbean has generated valuable evidence on women’s unpaid workloads and their relationship with gender inequalities. However, so far there is little information on rural women and the distribution of their time. This article analyzes some theoretical and methodological challenges that arise when measuring the time use of women living in rural and agricultural territories, based on the experience of designing and implementing a survey on time use in different regions of Argentina. Research carried out between 2022 and 2024 was systematized and, using a mixed methods approach, produced information on how rural women use time in the provinces of Córdoba, Tucumán, Santiago del Estero, and Mendoza. The results indicate that it is possible to design surveys that give meaning to their temporalities. In this sense, it is necessary to incorporate indicators to capture territorial particularities and ways of life and work, including, for example, the cyclicality of agricultural production, the simultaneity of tasks, the overlapping of spaces, workloads regarding self-consumption, and access to domestic services and technologies.